THE SHARE OF INTENSIVE AND EXTENSIVE FACTORS ON THE GDP DEVELOPMENT OF SELECTED EU COUNTRIES - Petr Wawrosz; Jiri Mihola (European Scientific Journal, ESJ, 2014)
The paper introduces new methodology how to count the share of intensive factors (total factors productivity) and extensive factors (total input factors, TIF) on the GDP development. The methodology is applicable for all possible developments and not only for growth of GDP as in case of growing accounting equation. The methodology is used for investigation of intensive and extensive development of selected EU countries with history of socialistic regime. The development of TIF is further divided on the development of labor and capital. The results are compared with results achieved for EU-15.